Proposed Methodology of Selection and Prioritization of New Product Development Using Analytic Hierarchi Process in PT XYZ - Rostianti, Dine; Dwi Lestari, Yuliani (The Indonesian Journal of Business Administration, 2016)
Abstract – Pharmaceutical industry in Indonesia has significant market growth potential, with a large and fast-growing population. The pharmaceutical industry is governed by strict regulations and covers every aspect of the activities of pharmaceutical companies, from the certification of production facilities; registration of new products and periodic re-registration of existing products; selection of suppliers; procurement and quality inspection of starting materials; development process of new products; development of analytical methods for checking the quality of starting materials, in-process control and finished products; handling of starting materials in the warehouse; controlling of drug production process that includes personnel, buildings, machinery, equipment, supporting utilities, procedures and documents; handling of finished products in the warehouse; controlling of drug distribution to authorized distribution channels; until post-marketing monitoring products. Meanwhile, there are limitations in the Indonesian market pharmaceutical industry for pharmaceutical products. For certain products listed in the national formulary, the BPJS Health policy resulted in the limitation of pharmaceutical industry market penetration to government and private health facilities. Drug services for participants of National Health Insurance in the health facilities refers to the list of drugs that are listed in the National Formulary with the price of drugs listed in the electronic catalog of drugs. The generic drug product development process from preparation to launch a new product takes a long time, generally is about three to five years. These factors of regulation, limited market and registrastion process need to be considered by PT XYZ as one pharmaceutical company in Indonesia. PT XYZ need to do a review to find the selection framework in new product development process. Problems that occur in the new product development process was diagnosed using a Current Reality Tree (CRT). Selection of new product candidates is based on criticality and urgency matrix. By using this matrix, of the 38 new product candidates in 2016 there are 6 products that fall into the first quadrant (high urgency, high criticality). These products are Product A (Quinolones 100 ml injection in softbag), Product B (Anti-amoebics 100 ml injection in softbag, Product C (Intravenous & Other Sterile Solutions Injection 500 mL A), Product D (Topical Corticosteroids oitment 10 gram), Product E (Topical Corticosteroids cream 10 gram), and Product F (Vitamin C tablets). The prioritization then performed using the Analytic Hierarchy Process (AHP) tool with BOCR (Benefits, Opportunities, Costs, and Risks) analysis to obtain a comprehensive consideration of various factors that affect the success of new products. The results of the pairwise comparison and sensitivity analysis shows the top three priorities are product F, product C and product D. Product F with a value of 0.316711 is the first priority to be done in 2016. The product C with a value of 0.171122 is the second priority and product D with a value of 0.169067 is the third priority. Keywords: Pharmaceutical Industry, New Product Development, selection and prioritization, Analytical Hierarchy Process, Benefits Opportunities Costs Risks Analysis.